2015
DOI: 10.1016/j.meatsci.2015.05.029
|View full text |Cite
|
Sign up to set email alerts
|

Development of microbial spoilage and lipid and protein oxidation in rabbit meat

Abstract: This experiment aimed to determine microbial spoilage and lipid and protein oxidation during aerobic refrigerated (4°C) storage of rabbit meat. Forty male New Zealand white rabbits were slaughtered according to the Halal slaughter procedure. The hind limbs were used for microbial analysis while the Longissimus lumborum m. was used for determination of lipid and protein oxidation. Bacterial counts generally increased with aging time and the limit for fresh meat (10(8)cfu/g) was reached at d 7 postmortem. Signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
35
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 62 publications
6
35
0
3
Order By: Relevance
“…Decreased tenderness as the ultimate pH of fat drops from 6.02 to 4.76 is due to the fat rancidity, microbial infection, storage time and other conditions of storage. These values are similar to those reported by Nakyinsige, K. et al 9 . The changes of pH value is indicate that the stability of the fat start to disintegrate.…”
Section: Changes In Phsupporting
confidence: 93%
See 2 more Smart Citations
“…Decreased tenderness as the ultimate pH of fat drops from 6.02 to 4.76 is due to the fat rancidity, microbial infection, storage time and other conditions of storage. These values are similar to those reported by Nakyinsige, K. et al 9 . The changes of pH value is indicate that the stability of the fat start to disintegrate.…”
Section: Changes In Phsupporting
confidence: 93%
“…This was probably due to the destruction of hydro-peroxides into secondary oxidation products and production of potentially toxic compounds. In the recently study 9 reported that the TBARS value of rabbit muscle along the storage period at 4 increased when the storage time increased for 7 days. Also, Elva 22 reported that TBARS in chicken leg and breast meat also increased at the end of 6 months of frozen storage.…”
Section: Changes In Pv and Tbarsmentioning
confidence: 93%
See 1 more Smart Citation
“…Nakyinsige et al. () and Rodríguez‐Calleja et al. () reported the spoilage of rabbit meat stored aerobically at 3 °С for 7 days, when the total microbial, psychrotrophic, and Pseudomonas counts attained 8 log cfu/g.…”
Section: Meatmentioning
confidence: 99%
“…Standard tests include total bacterial count (TBC) (Casaburi et al, 2015), rancidity measurements with thiobarbituric acid reactive substances assay (TBARS) (Nakyinsige et al, 2015), determination of VDCs by GC-MS and total volatile basic nitrogen (TVBN) measurements (Jaffrès et al, 2011). Colour evaluation and sensory descriptive analysis can be also useful in the detection of spoiled samples (Dissing et al, 2013).…”
Section: Spoilage Monitoringmentioning
confidence: 99%